Efeito da deleção do gene que codifica uma proteína de ligação à RNA sobre o transcriptoma de epimastigotas de Trypanosoma cruzi - Wanessa Moreira Goes (2018)
Trypanosoma cruzi, the etiological agent of Chagas' disease, is a protozoan that presents three forms during its life cycle, which are biochemically and morphologically distinct and programmed to respond quickly to the drastic environmental changes that this parasite faces in its various hosts. Unlike other eukaryotes, the genes encoding proteins in this protozoan are transcribed into polyrcistronic pre-mRNAs, which are processed into mature mRNAs by coupled trans-splicing and polyadenylation reactions. Because of this, control of gene expression depends primarily on post-transcriptional mechanisms mediated by RNA binding proteins (RBPs), which control steady-state levels and translation rates of mRNAs. RNA-seq of epimastigotes, trypomastigotes and amastigotes, together with searches for motifs characteristic of RBPs allowed the identification of a protein with increased levels of expression in the epimastigote form, when compared to amastigote and trypomastigote forms. This protein was named TcRBP99. Metacyclogenesis experiments comparing wild-type epimastigotes (WT) and epimastigotes in which the gene encoding TcRBP99 was deleted identified a role related to parasite differentiation since an increase in the rate of metacyclogenesis was observed in parasitic knockouts. Based on these data, the present work had the objective of analyzing the effect of the deletion of the gene encoding TcRBP99, in the control of the gene expression of epimastigote forms of T. cruzi, in order to identify genes whose expression would be associated with metacyclogenesis. RNA-seq analyzes were performed comparing the gene expression of WT epimastigotes and epimastigotes from two knockout lines for this RBP. cDNA libraries were sequenced on the Illumina MiSeq platform and then quality analyzes of the generated reads were conducted. Later, the reads were mapped against the complete genome of CL Brener, using the TopHat2 tool and differential gene expression analyzes using the following packages: EdgeR, limma and Deseq2. For the selection of differentially expressed genes (GDE), the parameters p-adjusted (padj) <0.05 and change of expression greater than or less than 2 times were defined. Finally, 3 'UTR regions were determined, allowing the identification of motifs, using the MEME and MAST tools. As a result, we obtained, on average, 3.6 million reads with quality based on the phred score equal to or greater than 20 for each of the seven libraries, and an average mapping of 73.28% of these reads. Differential expression analyzes revealed 9 genes that showed reduced expression in epimastigotes knockouts compared to WT: one of them codes for the differentiation-associated protein, whose mRNA is increased in WT epimastigotes compared to trypomastigotes and amastigotes. Three RHS family genes and one amino acid transporter coding gene also had diminished expression in the absence of TcRBP99. Analysis of motifs in 3' UTRs regions of these mRNAs showed that there are three conserved motifs, but none are present in the four UTRs at the same time. The results obtained in this work suggest that the TcRBP99, when binding to mRNAs in epimastigote forms causes the stabilization of these mRNAs, thus increasing the expression of genes responsible for the proliferation of epimastigotes, which consequently leads to a decrease in the rate of epimastigote differentiation for trypomastigotes metacyclic.